ACUTE ACALCULOUS CHOLECYSTITIS IN A CHILD WITH HEPATITIS A INFECTION - Ali, Joohi Zafar; Hussain, Shahid; Khan, Muhammad Athar; Khan, Rashid Naseem (Journal of Postgraduate Medical Institute, 2019)
Acute acalculous cholecystitis (AAC) is an unusual and atypical manifestation of acute viral hepatitis A which is endemic in many developing countries. It may cause gangrene and perforation of the gallbladder wall if not picked early but mortality from acute acalculous cholecystitis in these patients is far less than AAC of other origins that need surgical intervention. Usually conservative management helps improving the condition of these patients with hepatitis A virus (HAV) infection. Here we are going to present a case of a 7-year-old girl who was diagnosed with atypical cholecystitis clinically and on ultrasound examination.